Asabiyya: re-interpreting value change in globalized societies - Arno Tausch; Almas Heshmati (Institute for the Study of Labor (IZA), 2009)
This article reflects the renewed interest of economics and the social science discipline in value systems and religion. The World Values Survey provided a data framework of global value change, whose quantitative results led Barro (2004) to analyze the connections between some dimensions of recent sociological religious value research with economic growth. The present essay starts from this methodological position, and links value systems with economic performance in a much wider and macrosociological framework. We further develop the well-known Inglehart and Welzel (2003) map of global values, and develop the idea of Asabiyya (social cohesion), as a counter-model to both Barro and Inglehart and Welzel approaches. A frequently asked question is whether modernization without spiritual values in a globalized world economy and world society possible in the long run? Starting from principal component analysis, it is shown that rather two factors are decisive in understanding global value change: a continuum of traditional versus secular, and a continuum cheating versus active society. Asabiyya in the 21st Century, as a way out from the modernization trap of societies, characterized by large-scale social anomaly, is a high secularism combined with a high active society score, thus avoiding the modernization trap. We show that economic growth in the current world crisis is far more connected with these dimensions. We conclude that not a society based on fear is needed in the first place, but an active society of volunteer social work.
Keywords: C43; F5; Z12; D73; 330; Index numbers and aggregation; international political economy; religion; bureaucracy; corruption; Religion; Soziale Werte; Sozialer Wandel; Globalisierung; Public Choice; Wirtschaftswachstum; Welt